The Virtue of Hajj from a Hadith Perspective: The Study of Ma'anil Hadith - Nurasiah Jamil; Mulyana Mulyana (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to determine the understanding of hadith on the virtues of the pilgrimage. This research is a qualitative type that applies heritage studies by applying the ma'anil hadith method and historical analysis. The results and discussion of the study include the understanding of the pilgrimage, the hadith of the virtues of the pilgrimage, and the virtues of the pilgrimage in terms of various aspects. This study concludes that the virtue of Hajj is more important than Umrah. The wisdom of the pilgrimage is the positive values ​​or benefits contained in the pilgrimage that can be carried out by people who carry it out correctly and sincerely to Allah swt. The most prominent value of the pilgrimage is as an annual Mu'tamar.